MENGGAGAS FUNGSI-FUNGSI STRATEGIS LAYANAN CORNER DI PERPUSTAKAAN IAIN KUDUS - Radiya Wira Buwana (Fihris: Jurnal Ilmu Perpustakaan dan Informasi, 2021)
The IAIN Kudus library has three corner services that can be used by the entire academic community on the IAIN Kudus campus. The three corner services are the IAIN Kudus corner, the religious moderation corner, and the Asia Foundation corner. This study aims to find out what strategic functions can be applied to the corner service at the IAIN Kudus Library so that the corner service can support the role of the IAIN Kudus Library as a central source of information for the entire academic community at IAIN Kudus. This research was conducted with a descriptive research approach. The object of research is the three service corners in the IAIN Kudus Library. The data collection method used in this research is through observation data collection methods and data collection methods through literature studies. The observation data collection method was used by researchers to observe the corner services in the IAIN Kudus Library. Then the literature study used is through books and journal articles which according to the researcher are in accordance with the research theme. The data that has been obtained in this study were then analyzed descriptively. The results of this study indicate that the strategic functions that can be applied at the corner service of the IAIN Kudus Library include the identity function, deposit-promotive function, learning support function, collaborative function, and research function.